Executive Confidence: A Multidisciplinary Review, Synthesis, and Agenda for Future Research. (July 2022) - Heavey, Ciaran; Simsek, Zeki; Fox, Brian Curtis; Hersel, Matt C.
Over the past two decades, scholars of management, finance, accounting, economics, and entrepreneurship have studied the concept and implications of executive confidence in diverse settings. Despite sustained scholarly attention, numerous definitions, interpretations, and operationalizations of executive confidence present a problem for understanding past research and informing future progress. Equally problematic is that past research remains scattered across multiple disciplines, lacking a cohesive and comprehensive integration. Based on an in-depth review of 118 executive confidence studies and 268 studies in the wider confidence literature, we marshal the literature into four overarching themes for an encompassing understanding: (i) conceptualization of executive confidence, (ii) governance mechanisms and pathways of influence, (iii) implications and outcomes, and (iv) origins and antecedents. We leverage the insights of our review to discuss a richer conceptualization of executive confidence and chart an agenda for future research across each of the four themes of our review.